REFLECTIONS FROM DEATH FROM VOLUNTARY SELF-INJURY IN BRAZIL, 1996-2019. - Passos Santos, Maria Letícia; de Araújo Holanda, Acelino Neto; Matias Pires, Ana Carolina; Barbosa Martins , Bianca; Miranda Galvão, Flávia Letícia; Pinto Coelho, Glória Maria; Lima Feitosa Moreira, João Antônio Gonçalves; Carneiro Carvalho Gonçalves, Maria Luiza; Torres Hermenegildo de Souza, Há-Isis (Health and Society, 2022)
INTRODUCTION: Self-inflicted injuries may be classified suicidal behavior or self-harm. Regarding suicidal behavior, self-inflicted actions, which cause harm to the individual, involve ideation, attempt and suicide itself. Due to taboos related to suicide, public health problem and multifaceted psychosocial phenomenon, the perspectives of care and prevention are still limited in different health scenarios. This research aims to present a sociodemographic understanding of the phenomenon of suicide, promoting reflections that can improve therapeutic care, as well as subsidize preventive and health promotion proposals. METHODOLOGY: This is an ecological, descriptive and retrospective study whose methodology was the use of secondary data from the Mortality Information System (SIM). The sample consisted of all deaths secondary to voluntarily self-inflicted injuries, in Brazil, during the period 1996 to 2019, totaling 222,232 records. In the research, the following variables were used: Gender, Age, Color/Race, Marital Status and Education. RESULT AND DISCUSSION: men were the ones who died the most from self-harm and use more lethal methods to perform these injuries, although there are more suicide attempts among women. With regard to age group, most people who committed suicide were adults, aged between 20 and 59 years. However, it was noticed that the elderly and adolescents, in recent years, have become groups that are more vulnerable to suicide attempts. FINAL CONSIDERATIONS: there was an increase in the number of deaths from self-harm in Brazil among the years considered. It is noticeable that self-harm is a public health problem and requires adequate care and prevention interventions, in addition to structural changes related to risk factors.